Patient decision aids in knee replacement surgery. - Jayadev, C; Khan, T; Coulter, A; Beard, D; Price, A (2012)
Arthroplasty is an effective intervention for symptomatic knee osteoarthritis refractory to conservative therapy. However, recent data highlights regional variations in service provision unrelated to disease severity and a low, but not insignificant, rate of patient dissatisfaction. The variation in knee arthroplasty provision is in part also due to the clinical decision-making of orthopaedic surgeons. The management of osteoarthritis is an example of a preference-sensitive clinical pathway, and possible explanations for poor patient satisfaction include unrealistic expectations and poor perception of potential benefits and risks. In addition to the individual impact, this represents an inefficient use of resources by healthcare providers during a challenging economic period. Improved shared-decision making between patients and clinicians would potentially address these issues. Patient decision aids provide relevant personalized evidence-based information to facilitate the shared decision-making process. Orthopaedic surgeons are receptive to the use of patient decision aids to support shared decision-making, but there are a number of issues to overcome before they are routinely adopted. The number of decision aids and the literature supporting their effectiveness is growing rapidly. NHS Direct has launched online patient decision support for knee osteoarthritis. The use of patient decision aids in clinical practice is gathering pace and may soon become the ethical and legal standard. This article provides a narrative review of patient decision aids in the context of knee replacement surgery from a UK perspective.